The Influence of Institutional Ownership, Intellectual Capital, and Sales Growth on the Financial Performance of Real Estate and Property Companies - Fathiya Aulia Rahmah; Rini Destiana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates how sales growth, institutional ownership, and intellectual capital impact the financial performance of real estate and property companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2022. The Fixed Effect Model is used to perform quantitative analysis using panel data regression. The results of the analysis show that partially institutional ownership and intellectual capital do not have a significant effect on financial performance, while sales growth has a positive and significant effect. These findings suggest that, during the post-pandemic recovery phase, institutional ownership and intellectual capital did not have a significant influence. On the other hand, sales growth in the dense physical asset sector, such as property, is the factor that plays the most role in increasing profitability. Therefore, property businesses must prioritize strategies that increase sales, optimize transaction volumes, and improve operational efficiency by using digital tools. Human resource development and governance strengthening remain important for long-term competitive advantage, although they do not have a direct impact.